2015
DOI: 10.1080/07315724.2014.938183
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Oxidized and Partially Hydrogenated Oils Differentially Induces Trans-Fatty Acids Incorporation in Rats' Heart and Dyslipidemia

Abstract: In conclusion, process-induced TFAs cause changes including proatherogenic plasma lipid markers, heart fatty acid profiles, and coronary artery histology depending on the TFA level in the supplemented fat and therefore on the type of technological process used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(46 reference statements)
3
0
0
Order By: Relevance
“…The obtained results came in agreement with Aronis et al [40]who suggested that an improvement of lipid metabolism disorders and also worst in insulin resistance in TFAs and HFD groups suffered from obesity. Lp (a) level was markedly increased in the trans group and this result was in agreement with Dhibi et al [41]. They reported the inflammatory impacts and endothelial dysfunction after PHVO consumption which has been shown to induce accumulation of inflammatory cells, linked with increased activity of Lp (a), inducing cardiovascular risk and atherosclerotic.…”
Section: Discussionsupporting
confidence: 89%
“…The obtained results came in agreement with Aronis et al [40]who suggested that an improvement of lipid metabolism disorders and also worst in insulin resistance in TFAs and HFD groups suffered from obesity. Lp (a) level was markedly increased in the trans group and this result was in agreement with Dhibi et al [41]. They reported the inflammatory impacts and endothelial dysfunction after PHVO consumption which has been shown to induce accumulation of inflammatory cells, linked with increased activity of Lp (a), inducing cardiovascular risk and atherosclerotic.…”
Section: Discussionsupporting
confidence: 89%
“…The high intake of TFA in rats fed HVF diet was re ected in the increased TFA deposition in the tissues as also reported by Dhibi et al, 48 and in the occurrence of histological atherosclerotic lesions. In this context, HVF diet caused an increase of pro-in ammatory serum cytokines IL-1β and TNF-α cytokines.…”
Section: Discussionsupporting
confidence: 79%
“…Dietary intake of TFA was translated directly into an increased TFA concentration in the liver, heart and adipose tissue, as also reported by Dhibi et al 54 . The lower accumulation of adipose tissue in the HVF group suggests that our research procedures may have predisposed the rats to the onset of non-alcoholic fatty liver disease (NAFLD), as confirmed by the histopathologic analysis of hepatic tissue.…”
Section: Discussionsupporting
confidence: 74%